2023
DOI: 10.3389/fbioe.2023.1124995
|View full text |Cite
|
Sign up to set email alerts
|

Development of stromal differentiation patterns in heterotypical models of artificial corneas generated by tissue engineering

Abstract: Purpose: We carried out a histological characterization analysis of the stromal layer of human heterotypic cornea substitutes generated with extra-corneal cells to determine their putative usefulness in tissue engineering.Methods: Human bioartificial corneas were generated using nanostructured fibrin-agarose biomaterials with corneal stromal cells immersed within. To generate heterotypical corneas, umbilical cord Wharton’s jelly stem cells (HWJSC) were cultured on the surface of the stromal substitutes to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…In the first place, we generated fibrin-agarose biomaterials following previously described protocols ( Blanco-Elices et al, 2023 ). Briefly, to generate 1 mL of biomaterial, we mixed 760 µL of human plasma with 15 µL of tranexamic acid (Amchafibrin 5 mg/mL, MEDA Pharma SL, Madrid, Spain), 100 µL of a 2% solution of agarose in PBS (Merck), 50 µL of a 1% solution of CaCl 2 (Merck), and 75 µL of DMEM-Advanced culture medium (Thermo Fisher Scientific-Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…In the first place, we generated fibrin-agarose biomaterials following previously described protocols ( Blanco-Elices et al, 2023 ). Briefly, to generate 1 mL of biomaterial, we mixed 760 µL of human plasma with 15 µL of tranexamic acid (Amchafibrin 5 mg/mL, MEDA Pharma SL, Madrid, Spain), 100 µL of a 2% solution of agarose in PBS (Merck), 50 µL of a 1% solution of CaCl 2 (Merck), and 75 µL of DMEM-Advanced culture medium (Thermo Fisher Scientific-Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that the combination of these two biomaterials resulted in a significant improvement in both biological and biomechanical properties of the hydrogel and allowed the generation of a wide variety of artificial substitutes [16][17][18]. In fact, this model has already shown promising preclinical results in multiple scenarios such as skin [15], cornea [19] and oral mucosa [18] grafting and as a nerve repair strategy [17], which allowed its successful translation to clinical practice [16]. However, this is the first time this hydrogel has been used to recreate complex pathological processes such as NI.…”
Section: Histological Analysis Of Neural Invasion Models Using Hemato...mentioning
confidence: 99%